2013
DOI: 10.5350/semb2013470204
|View full text |Cite
|
Sign up to set email alerts
|

Yoğun bakım ünitemizdeki intoksikasyon olgularının geriye dönük incelenmesi

Abstract: ÖZET:Diferansiye tiroit kanserlerinde TNM evreleme sisteminin 8. sürümünde neler değişti? Klinik pratiği nasıl etkileyecek?TNM evreleme sisteminin son olarak sekizinci sürümü (edisyonu) yayınlandı. Tiroit kanserleri TNM evreleme sisteminin 1987 yılında yayınlanan 4. sürümünde yer aldı. Literatürdeki kanıtlara dayalı olarak güncellenen TNM sisteminin her sürümü diğer kanserler gibi diferansiye tiroit kanserleri (DTC) için de bir önceki sürümüne göre önemli bazı farklılıklar içerir. Tiroit kanserleri için günümü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…It has been mentioned in similar studies that a significant portion of those attempting suicide have previously been diagnosed with a psychiatric disorder (7,9). Especially in cases of depressive disorders, a high occurrence of suicide attempts is noted, often involving medications used in their treatment.…”
Section: Discussionmentioning
confidence: 96%
“…It has been mentioned in similar studies that a significant portion of those attempting suicide have previously been diagnosed with a psychiatric disorder (7,9). Especially in cases of depressive disorders, a high occurrence of suicide attempts is noted, often involving medications used in their treatment.…”
Section: Discussionmentioning
confidence: 96%
“…In different studies, intoxication mortality rates range between 0.2% and 23.5% [7] [14] [16] [24]. Kose et al showed that 29.4% of the patients needed mechanical ventilation support and the mortality rater in their findings was 23.5% [25].…”
Section: Discussionmentioning
confidence: 99%
“…Medical drugs has been reported as the most common cause of intoxication, both in studies conducted in different countries of the world and in our country. It was previously reported that the antidepressants, antibiotics, analgesics, benzodiazepines are the most frequently used drugs, in different proportions[7] [8] [9][13] [14] [15][16]…”
mentioning
confidence: 99%
“…Bunun yanında pestisitlerden tarım ilacı, fare zehiri, koroziv maddelerden çamaşır suyu, tuz ruhu, akü suyu ve kolonya ayrıca karbonmonoksit inhalasyonu ve yılan sokması ise diğer intoksikasyon nedenleri arasındaydı. Literatürde bulunan ve ülkemizde farklı illerde yapılmış olan çalışmalarda da intihar girişimi için benzer sıklıkta ve aynı grup ilaçların kullanıldığı bildirilmiştir (9,10). İntoksikasyon tek ilaç veya kimyasal madde ile gerçekleşebileceği gibi birden fazla madde ve/veya ilaç alarak da meydana gelebilir.…”
Section: Bulgularunclassified